1978
DOI: 10.1007/bf01809134
|View full text |Cite
|
Sign up to set email alerts
|

The significance for diagnosis and for surgical technique of multiple aneurysms of the same internal carotid artery

Abstract: A small series of five patients with more than one aneurysm on the same internal carotid artery is reported. The author believes that similar cases must have been observed by many neurosurgeons but can find no specific reference to the technical and diagnostic problems created by such lesions. Sometimes these lesions can be clipped separately, but when the aneurysms are contiguous it may be helpful to apply a clip with its jaws parallel to the long axis of the internal carotid artery. The author suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…Jefferson et al 1) first reported five cases of KA mutually contacting the same internal carotid artery in 1978, and in 1984, Yasargil 2) named two aneurysms occurring upon mutually contacting the same internal carotid artery KA. because the first placed coil was in the way when embolizing the second aneurysm following embolization of the first aneurysm, making it difficult to confirm the branch as well as making identification of the neck and parent blood vessel of the second aneurysm difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jefferson et al 1) first reported five cases of KA mutually contacting the same internal carotid artery in 1978, and in 1984, Yasargil 2) named two aneurysms occurring upon mutually contacting the same internal carotid artery KA. because the first placed coil was in the way when embolizing the second aneurysm following embolization of the first aneurysm, making it difficult to confirm the branch as well as making identification of the neck and parent blood vessel of the second aneurysm difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Kissing aneurysms (KAs) are caused when two aneurysms with different cervixes mutually contact each other, having first been reported by Jefferson et al in 1978. 1) In 1984, Yasargil 2) named such aneurysms as KAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen cases of kissing aneurysms including the present case have been reported 2,3,[5][6][7][8][9] (Table 1). Four patients were males and 14 were females, aged from 26 to 59 years (mean 44.7 yrs) with SAH and 21 to 60 years (mean 46.3 yrs) without SAH.…”
Section: Discussionmentioning
confidence: 99%
“…This particular type of multiple aneurysms requires caution in diagnosis and surgical management. 2) Kissing aneurysms are sometimes misinterpreted as the bleb of an aneurysmal dome or atherosclerotic single multiloculated aneurysm. A large series of intracranial aneurysms identified two of 1012 cases (0.2%) with kissing aneurysms.…”
Section: Introductionmentioning
confidence: 99%